Facile Synthesis and Catalytic Activity Assessment of Copper Chromite Nanoparticles for Ammonium Perchlorate Decomposition. Issue 1 (1st August 2022) - Ismael, Shukri; Deif, A; Maraden, Ahmed; Elbasuney, Sherif
Abstract: The universal burning rate modifier used in composite solid propellants is copper chromite. The fabrication of copper chromite nanoparticles (CCNs) is highly appreciated; as superior performance could be accomplished. This research looks at how copper chromite nanoparticles can be made in a sustainable way using hydrothermal processing. Mono-dispersed particles with a medium particle size of 12 nm were seen in TEM micrographs. The XRD diffractogram revealed a crystalline structure. The co-precipitation approach was used to incorporate CCNs into ammonium perchlorate (AP). Differential scanning calorimetry (DSC) and thermal gravimetric analysis were used to analyze the activity of catalysis in CCNs on AP breakdown (TGA). The enthalpy of AP breakdown was enhanced from 742 J/g to 1391 J/g. CCNs caused the Peak of high-temperature decomposition shift toward lower temperatures, resulting in the overlapping of the two peaks into a single peak. At 244 °C, CCNs showed a decrease in AP endothermic phase transition. These characteristics could ensure high-burning-rate catalyzed decomposition processes.